Biochar amendment to lead‐contaminated soil: Effects on fluorescein diacetate hydrolytic activity and phytotoxicity to rice. (7th July 2015) - Tan, Xiaofei; Liu, Yunguo; Gu, Yanling; Zeng, Guangming; Hu, Xinjiang; Wang, Xin; Hu, Xi; Guo, Yiming; Zeng, Xiaoxia; Sun, Zhichao
Abstract The amendment effects of biochar on total microbial activity was measured by fluorescein diacetate (FDA) hydrolytic activity, and phytotoxicity in Pb(II)‐contaminated soils was examined by the application of 4 different biochars to soil, with rice as a test plant. The FDA hydrolytic activities of biochar‐amended soils were much higher than that of the control. The survival rate of rice in lead‐contaminated biochar‐amended soils showed significant improvement over the control, especially for bamboo biochar‐amended soil (93.3%). In addition, rice grown in lead‐contaminated control sediment displayed lower biomass production than that in biochar‐amended soil. The immobilization of Pb(II) and the positive effects of biochar amendment on soil microorganisms may account for these effects. The results suggest that biochar may have an excellent ability to mitigate the toxic effects of Pb(II) on soil microorganisms and rice. Environ Toxicol Chem 2015;34:1962–1968. © 2015 SETAC